LEGAL PROTECTION COUNSELING FOR DOMESTIC VIOLENCE IN LAU GUMBA VILLAGE - Maria Ferba Editya S; Icha Florensia; Jimmy Prisma; Rocky Batanta (Suluh Adiluhung Publisher (SAPub), 2024)
The crime of domestic violence (KDRT) is a complex and multifaceted crime. The problem of domestic violence itself is actually a problem that often occurs in married life, but some people do not consider what they experience as a wrong act in the eyes of the law. Therefore, the public needs to be given an understanding of domestic violence, so that if domestic violence occurs or experiences, the victim can take legal steps. This outreach activity in the community is motivated by phenomena that occur in the community. The method used is a participatory method which is expected to play an active role in legal education activities in the form of; (1) Socialization in legal education regarding Law Number 23 of 2004 concerning Domestic Violence; (2) Question and answer session about domestic violence.